Stress tolerance and heritability in dill (Anethum graveolens) lines from central and western India under contrasting soil sodicity environments - GAUTAM, R K; CHAUHAN, M S; PANESAR, B; NAYAK, A K; SHARMA, D K; QADAR, A; SINGH, GURBACHAN (The Indian Journal of Agricultural Sciences, 2011)
Dill (Anthum graveolens L.) crop is tolerant to salinity and its adaptation under sodic soils was not previously reported. Therefore, the present study was conducted during 2005–07 at two locations (Karnal and Lucknow) to identify sodicity tolerant genotypes and to elucidate parameters of genetic variability and nature of inter-relationships among various traits affecting the seed yield in dill in sodic soils. Eleven genotypes of dill were evaluated under three environments (normal, moderate sodic pH2 9.5 and high sodic pH2 9.8) during winter (rabi) 2005–06 and 2006–07. Among all collections,‘CSS 1’ was found to exhibit highest seed yield across three years under different alkalinity locations. The trait number of inflorescence/plant showed maximum sensitivity, followed by seed yield, plant height, primary and secondary branches and plant stand in almost both stress regimes. In the moderate sodic soil there was low genotypic coefficent of variation, high heritability, high genetic advance and a positive and significant correlation of secondary branches, primary branches and inflorescence number with seed yield. These traits also exercised relatively higher direct effects. Thus, further genetic improvement in this hardy crop under high sodic environment can be achieved using indirect selections for these traits.